-2x-66=62-10x

Simple and best practice solution for -2x-66=62-10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-66=62-10x equation:


Simplifying
-2x + -66 = 62 + -10x

Reorder the terms:
-66 + -2x = 62 + -10x

Solving
-66 + -2x = 62 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-66 + -2x + 10x = 62 + -10x + 10x

Combine like terms: -2x + 10x = 8x
-66 + 8x = 62 + -10x + 10x

Combine like terms: -10x + 10x = 0
-66 + 8x = 62 + 0
-66 + 8x = 62

Add '66' to each side of the equation.
-66 + 66 + 8x = 62 + 66

Combine like terms: -66 + 66 = 0
0 + 8x = 62 + 66
8x = 62 + 66

Combine like terms: 62 + 66 = 128
8x = 128

Divide each side by '8'.
x = 16

Simplifying
x = 16

See similar equations:

| 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 | | 3m^2-7m-40=0 | | -126+9x=39-2x | | -12-2x=-20 | | -93+4x=-6x+107 | | 4y=6y-12 | | 7x^2+3x+88=180 | | -x-21=-5x+19 | | -2(-4+7x)+8x=3 | | 25+40x=50+20x | | 6x-3=-3-4x |

Equations solver categories